Weed Control and Winter Wheat Crop Yield With the Application of Herbicides, Nitrogen Fertilizers, and Their Mixtures With Humic Growth Regulators - Irina Korotkova; Mykola Marenych; Volodymyr Hanhur; Oksana Laslo; Oksana Chetveryk; Viktor Liashenko (Acta Agrobotanica, 2021)
The aim of the present study was to determine the efficacy of the application of mixtures containing various combinations of humic substances, with herbicides and nitrogen fertilizers, in weed control and optimizing the plant nutrition system. We also aimed to evaluate the influence of these substances on winter wheat productivity. Five Ukrainian winter wheat cultivars (‘Kryzhynka,’ ‘Smuhlyanka,’ ‘Slavna,’ ‘Kubus,’ and ‘Mulan’) were sown in a randomized complete block design, with three replications, in the years 2014–2019. The analysis of the effect of the compositions containing herbicides, with various physiologically active substances, in a mixture with humic preparations (Humifield, 4R Foliar concentrate) was performed by counting weeds per square meter in each experimental plot. The best performance in weed control, including perennial species, was obtained from using a mixture of Grodil Maxi herbicide with the humic preparation, Humifield. The crop treatment of this mixture resulted in a 23.6% reduction in weeds, compared to the treatment with the Grodil Maxi herbicide only. At the same time, the complex application of a number of herbicides in a mixture with the humic preparation, 4R Foliar concentrate led to the opposite effect. Various applications of mixtures of humates (4R Foliar concentrate, 5R SoilBoost) with nitrogen fertilizers (ammonium nitrate; carbamide-ammonium mixture) to optimize the winter wheat nutritional system and yield increases have been studied. The highest yield increase of 20%–22% was harvested in the plots treated with 5R SoilBoost and 4R Foliar concentrate plus ammonium nitrate. In addition, the efficacy of wheat crop foliar feeding with mixtures of humates, plus a carbamide-ammonia mixture, in different phases of vegetation has been established. A yield increase of 10.0%–21.4% resulting from the use of such compositions was obtained.